HLA genotyping using the Illumina HLA TruSight next‐generation sequencing kits: A comparison. (28th May 2017) - Profaizer, T.; Lázár‐Molnár, E.; Pole, A.; Delgado, J. C.; Kumánovics, A.
Summary: Illumina first introduced their TruSight human leucocyte antigen (HLA) next‐generation sequencing (NGS) typing kit in 2015 and subsequently followed up with a new version in 2016. Here we report on our experience comparing the two versions of the Illumina HLA NGS kits.